Thalia delighting in song : essays on ancient Greek poetry - Robbins, Emmet, 1939-2011 (Phoenix. Supplementary volume, 2013)
Thalia Delighting in Song ensures that the next generation of Classicists will continue to benefit from the insights of one of the foremost scholars in the field.